Building Adolescent Assertiveness Awareness Through Individual Counseling Services: A Psychoeducational Approach - Danni, Ulfa; Ahmad, Fitri (Jurnal Profesi Pendidikan, 2025)
Adolescents often face difficulties in expressing thoughts and feelings appropriately, which indicates low assertiveness awareness. Lack of assertiveness can lead to social pressure, interpersonal conflict, and decreased psychological well-being. This study aims to examine how individual counseling services with a psychoeducational approach can build assertiveness awareness in adolescents. This study uses a literature review design by examining scientific sources from relevant national and international journals in the past five years. The search procedure was carried out through databases such as Google Scholar, ResearchGate, and ScienceDirect using the keywords "assertiveness," "adolescents," individual counseling," and "psychoeducation." Selection was carried out based on the relevance, recency, and methodological quality of the articles. Data are presented thematically and analyzed descriptively-qualitatively. The results of the study indicate that the psychoeducational approach in individual counseling is effective in increasing adolescent assertiveness awareness and skills. Individual counseling allows for the delivery of personalized material, while psychoeducation provides conceptual and practical understanding related to assertive behavior. In conclusion, the integration of the psychoeducational approach in individual counseling can be an effective strategy for building adolescent assertiveness awareness holistically.